How client attachment affects information verification in commercial valuation practice. Issue 6 (2nd September 2019) - Klamer, Pim; Gruis, Vincent; Bakker, Cok
Abstract : Purpose: Information verification is an important factor in commercial valuation practice. Valuers use their professional autonomy to decide on the level of verification required, thereby creating an opportunity for client-related judgement bias in valuation. The purpose of this paper is to assess the manifestation of client attachment risks in information verification. Design/methodology/approach: A case-based questionnaire was used to retrieve data from 290 commercial valuation professionals in the Netherlands, providing a 15 per cent response rate of the Dutch commercial valuation population. Descriptive and inferential statistics have been used to test research hypotheses involving relations between information verification and professional features that may indicate client attachment such as an executive job level and brokerage experience. Findings: The results reveal that valuers acting at partner level within their organisation obtain lower scores on information verification compared to lower-ranked valuers. Also, brokerage experience correlates negatively to information verification of valuation professionals. Both findings have statistical significance. Research limitations/implications: The results reflect valuers' reasoning behaviour rather than actual behaviour. Replication of findings through experimental design will contribute to research validity. Practical implications: Maintaining close client contact in a competitive environment is important for business continuity yet may foster client attachment. The associated downside risks in valuation practice call for higher awareness of (subconscious) client influence and the development of attitudinal scepticism in valuer training programmes. Originality/value: This paper is one of the few that explore possible sources of valuer judgement bias by relating client-friendly valuer features to a key area of valuation i.e. information verification.